Management of Chronic Myeloid Leukemia in Advanced Phase - Bonifacio, Massimiliano; Stagno, Fabio; Scaffidi, Luigi; Krampera, Mauro; Di Raimondo, Francesco (Frontiers in Oncology, 2019)
Management of chronic myeloid leukemia (CML) in advanced phases remains a challenge also in the era of tyrosine kinase inhibitors (TKIs) treatment. Cytogenetic clonal evolution and development of resistant mutations represent crucial events that limit the benefit of subsequent therapies in these patients. CML is diagnosed in accelerated (AP) or blast phase (BP) in <5% of patients, and the availability of effective treatments for chronic phase (CP) has dramatically reduced progressions on therapy. Due to smaller number of patients, few randomized studies are available in this setting and evidences are limited. Nevertheless, three main scenarios may be drawn: (a) patients diagnosed in AP are at higher risk of failure as compared to CP patients, but if they achieve optimal responses with frontline TKI treatment their outcome may be similarly favorable; (b) patients diagnosed in BP may be treated with TKI alone or with TKI together with conventional chemotherapy regimens, and subsequent transplant decisions should rely on kinetics of response and individual transplant risk; (c) patients in CP progressing under TKI treatment represent the most challenging population and they should be treated with alternative TKI according to the mutational profile, optional chemotherapy in BP patients, and transplant should be considered in suitable cases after return to second CP. Due to lack of validated and reliable markers to predict blast crisis and the still unsatisfactory results of treatments in this setting, prevention of progression by careful selection of frontline treatment in CP and early treatment intensification in non-optimal responders remains the main goal. Personalized evaluation of response kinetics could help in identifying patients at risk for progression.